2016
DOI: 10.1371/journal.pone.0166554
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke after Herpes Zoster – Evidence from a German Self-Controlled Case-Series Study

Abstract: BackgroundHerpes zoster (HZ) is caused by reactivation of the latent varicella-zoster virus (VZV). A severe complication of HZ is VZV vasculopathy which can result in ischemic or hemorrhagic stroke. The aims of our study were to assess the risk of stroke after the onset of HZ and to investigate the roles of stroke subtype, HZ location and the time interval between HZ onset and stroke.MethodsA self-controlled case-series study was performed on a cohort of patients with incident stroke recorded in the German Pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…Decades later, the latent virus can be reactivated and result in herpes zoster (HZ) which is usually characterised by a painful skin rash 2 . Since the reactivation of the VZV is typically associated with a decline in cell-mediated immunity, older and immunocompromised (IC) individuals are at higher risk of developing HZ and its complications like postherpetic neuralgia (PHN) and VZV vasculopathy [2][3][4][5][6][7][8][9] . Accordingly, a recently published systematic review reported an HZ incidence rate (IR) between 6 and 8 per 1,000 person-years (py) in 60-year-olds and between 8 and 12 per 1,000 py at age 80 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Decades later, the latent virus can be reactivated and result in herpes zoster (HZ) which is usually characterised by a painful skin rash 2 . Since the reactivation of the VZV is typically associated with a decline in cell-mediated immunity, older and immunocompromised (IC) individuals are at higher risk of developing HZ and its complications like postherpetic neuralgia (PHN) and VZV vasculopathy [2][3][4][5][6][7][8][9] . Accordingly, a recently published systematic review reported an HZ incidence rate (IR) between 6 and 8 per 1,000 person-years (py) in 60-year-olds and between 8 and 12 per 1,000 py at age 80 10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the epidemiology of HZ in Asian RA patients, and the association between HZ and immunosuppressive agents in RA patients is controversial. In addition, several epidemiologic studies have demonstrated an increased risk of stroke after HZ . A recent systematic review and meta‐analysis showed that the risk of stroke is higher in patients with RA than in the general population .…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents an overview of the eight retrospective cohort studies [ 22 30 ] and three self-case controlled case series [ 31 33 ] included in this review. We included self-controlled case series since these studies have a design akin to that of an efficient cohort study that minimizes confounding and produces measures of association, unlike a traditional case series [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…We included self-controlled case series since these studies have a design akin to that of an efficient cohort study that minimizes confounding and produces measures of association, unlike a traditional case series [ 34 ]. The studies sampled populations from six countries including enrollees of the national health insurance systems in Taiwan [ 23 , 25 , 28 , 29 ] and South Korea [ 24 ], Danish hospital and prescription drug users [ 26 ], British primary care patients [ 22 , 31 ], American Medicare enrollees 65 years and older [ 32 ], residents 50 years and older in Olmsted County (MN, US) [ 30 ], enrollees of four private insurers in Germany [ 33 ] and residents of Västra Götaland County, Sweden [ 27 ]. All included studies performed retrospective reviews of electronic medical record databases; no study prospectively followed patients.…”
Section: Resultsmentioning
confidence: 99%